Perancangan Enterprise Architecture untuk Integrasi Proses Operasional Board Game Cafe Menggunakan TOGAF ADM: Studi Kasus Gameopoly - Muhammad Aghnat Mumtaz; Ahmad Abdul Faqih; Kenanya Otniel Suhardi; Oktavian Luthfi Khairan Somali; Afifah Trista Ayunda (Jurnal Nasional Komputasi dan Teknologi Informasi, 2026)
Gameopoly Board Game Cafe provides services that go beyond food and beverage sales, including board game management, customer assistance by Game Masters, and operational reporting. This condition requires an architectural design that connects business processes, data, applications, and technology in an integrated manner. This study aims to design Gameopoly’s Enterprise Architecture using TOGAF ADM. A qualitative case study method was applied through semi-structured interviews with the owner and the head of Game Masters. The result is an Enterprise Architecture blueprint covering Business Architecture, Data Architecture, Application Architecture, Technology Architecture, Opportunities and Solutions, and Implementation Governance. The design produces a to-be business process, conceptual data model, ArchiMate model, and phased implementation roadmap. The proposed blueprint can serve as a foundation for information system development to support food and beverage ordering, board game inventory, Game Master services, and operational reporting integration.